2008
DOI: 10.1016/j.mambio.2007.10.010
|View full text |Cite
|
Sign up to set email alerts
|

First reports of XXY aneuploidy in natural populations of Thomas’ pine vole Microtus thomasi (Rodentia: Arvicolidae) from Greece

Abstract: As part of an extensive cytological study in natural populations of Thomas' pine vole Microtus thomasi, two cases of XXY aneuploidy (2n ¼ 45, FN ¼ 47) from different localities of NW Peloponnesus, Greece were recently recorded. These constitute the first report of sex chromosome aneuploidy for this species, in a sample of 366 individuals from 89 localities of Greece. Both individuals appeared with a male phenotype and normal morphology; however, measurements and histological examination in the testes of one of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 46 publications
1
16
0
Order By: Relevance
“…atticus with 2n = 38-44 (one individual had 2n = 45 (XXY)) and different sex chromosome constitutions, as described by Rovatsos et al [2008] ( fig. 3 ; table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…atticus with 2n = 38-44 (one individual had 2n = 45 (XXY)) and different sex chromosome constitutions, as described by Rovatsos et al [2008] ( fig. 3 ; table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…a Refers to the population numbers in figure 1. b Chromosomal races according to Rovatsos [2012]. c This R32 individual has 2 X st1 and 1 Y 1 [Rovatsos et al, 2008].…”
Section: Southern Blotmentioning
confidence: 99%
“…hybrids between the karyomorphs M. thomasi 'thomasi' and 'atticus' Rovatsos et al, 2008) suggest that these two could be considered as different local populations of the same species. Several studies have demonstrated that amplification of repetitive DNA sequences on sex chromosomes of Microtus species gives rise to blocks of constitutive heterochromatin (Kozlova et al, 2003;Marchal et al, 2004aMarchal et al, , b, 2006Acosta et al, 2008), possibly through different, independent and rapid processes in each species.…”
Section: Mth-alu900-con Actggtcaaaccggttta---------------------------mentioning
confidence: 99%
“…Among other mammals, XXY males have been shown to be particularly frequent in wild Microtus voles; for example, in a total of 630M. arvalis and M. thomasi, there were six sex chromosome aneuploids of which half had the XXY condition (Zima et al 1992;Rovatsos et al 2008). However, unlike the house mouse, both M. arvalis and M. thomasi have asynaptic X-Y pairing during meiosis and this may lead to a high incidence of sex chromosome aneuploidy, including occurrence of XXY individuals.…”
Section: Discussionmentioning
confidence: 99%
“…An XXY karyotype has very rarely been recorded in wild mammals, but there are reports for the tammar wallaby (Macropus eugenii; Sharman et al 1970), common shrew (Sorex araneus; Searle 1984), common vole (Microtus arvalis; Zima et al 1992) and Thomas' pine vole (Microtus thomasi; Rovatsos et al 2008). …”
Section: Introductionmentioning
confidence: 99%